High femoral bone mineral density accretion in prepubertal soccer players - Vicente-Rodriguez, G.; Ara, I.; Perez-Gomez, J.; Serrano-Sanchez, J. A.; Dorado, C.; Calbet, J. A. L. (Medicine & Science in Sports & Exercise, 2004)
Purpose: To determine the effect of physical activity on bone mineral accrual during growth in prepuberal boys. Methods: Seventeen soccer players and 11 matched (physically active) control boys (Tanner 1-2, at the start of the study) were followed over a 3-yr period. Bone mineral content (BMC) and areal density (BMD) was measured by dual-energy x-ray absorptiometry. The maximal positive mechanical impulse (CJipos) and height jumped (Hj) during countermovement vertical jumps were assessed with a plate force. Additionally, 30-m running speed test (T30), 300-m run test (AC), and 20-m shuttle run test (MAP) were performed. Results: The soccer players attained better results in MAP and AC than the controls (P < 0.05). At the end of the follow-up, the controls increased their percentage of body fat in 11 units (P < 0.05) whereas it remained unchanged in the soccer players. Lean body mass increased with growth but more in the soccer players than in the controls (P < 0.05). The soccer players exhibited greater BMC in the legs and greater BMD in all bone-loaded regions at the end of the study (P < 0.05). During these 3 yr, the soccer players gained twice as much femoral neck and intertrochanteric BMC than the control group (P < 0.05) and increased their femoral neck BMD by 10% and their mean hip BMD by a third more than the control group (both P < 0.05). Multiple regression analysis showed that the improvement in T30 and CJipos has predictive value for the enhancement of bone mass in growing boys. Conclusion: Long-term soccer participation, starting at a prepubertal age, results in greater improvement of physical fitness, greater acquisition of bone mass and a lower accumulation of body fat.